The Reuse of Red Imperial Porphyry in the West from the End of the Ancient World - Licordari, Francesca (Actual Problems of Theory and History of Art, 2022)
The red imperial porphyry is a rare, appreciated and expensive marble of the antiquity. The ideology of imperial power is symbolically expressed by the purple color. Therfore, the Porphyry, for the obvious chromatic similarity, is closely linked with the concept of royalty. This combination was transmitted not only to Byzantium, which is direct continuation of the Empire. It was also used in more recent times, whenever there was the need to emphasize the sacredness of power (in the Church, in the time of Carolingian Empire, of the Ottonian dynasty, of the Norman kings of Sicily, of the Swabian emperors or in the Ottoman Empire).Throughout the Middle Ages the difficulty of working the porphyry, a very hard marble, meant that almost all reused pieces were fragmentary: this is the case of the basins, reused as sepulchres or inserted in the altars, of the columns reused in the churches, of elaboration of the floor decorations (rotae porphyreticae, Cosmatesque floors) and so on.Only in the Renaissance the techniques of porphyry working were rediscovered. In Florence, the material was very popular among the artists of the court of the Medici. Soon after, the use of the material spread to the French court, and it also found great success among the families of the European nobility.The last attempt to revive the use of the ancient porphyry was made between the middle of the 19th century and the middle of the 20th century, but it failed due to the impossibility of finding blocks of good quality and sufficient size. In addition, the new European porphyries were now available at more competitive prices and therefore there was no extensive use of this ancient material, which thus acquired more and more prestige.
Keywords: red porphyry; reuse; sarcophagi; columns; basins; royalty